1999
DOI: 10.1084/jem.189.2.219
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12 Protects from a T Helper Type 1–mediated Autoimmune Disease, Experimental Autoimmune Uveitis, through a Mechanism Involving Interferon γ, Nitric Oxide, and Apoptosis

Abstract: Pathogenic effector T cells in experimental autoimmune uveitis (EAU) are T helper type 1–like, and interleukin (IL)-12 is required for their generation and function. Therefore, we expected that IL-12 administration would have disease-enhancing effects. Mice were immunized with a uveitogenic regimen of the retinal antigen interphotoreceptor retinoid-binding protein, treated with IL-12 (100 ng/d for 5 d), and EAU was assessed by histopathology. Unexpectedly, IL-12 treatment failed to enhance EAU in resistant str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
126
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(140 citation statements)
references
References 68 publications
14
126
0
Order By: Relevance
“…That idea is supported by a report describing that administration of IL-12 is protective in an experimental autoimmune uveitis model (34). The protection involved hyperinduction of IFN-␥, which causes an up-regulation of iNOS and production of NO (34). In fact, in the present study, we were able to demonstrate that iNOS is involved in the limitation of a Th1-mediated DTH response and acts most likely as the effector molecule downstream of IFN-␥.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…That idea is supported by a report describing that administration of IL-12 is protective in an experimental autoimmune uveitis model (34). The protection involved hyperinduction of IFN-␥, which causes an up-regulation of iNOS and production of NO (34). In fact, in the present study, we were able to demonstrate that iNOS is involved in the limitation of a Th1-mediated DTH response and acts most likely as the effector molecule downstream of IFN-␥.…”
Section: Discussionsupporting
confidence: 76%
“…That idea is supported by a report describing that administration of IL-12 is protective in an experimental autoimmune uveitis model (34). The protection involved hyperinduction of IFN-␥, which causes an up-regulation of iNOS and production of NO (34).…”
Section: Discussionsupporting
confidence: 58%
“…It has been proposed that NO represents a downstream mediator of IFN-c action and plays an important role in T cell homeostasis and ultimately the down-regulation of some Th1-mediated inflammation [17,22,25]. NO has been shown to have various immunosuppressive actions on T cells, inhibiting T cell proliferation and secretion of cytokines and increasing T cell apoptosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has recently been shown that IFN-c likely influences the effector phase of a T cell-mediated response by limiting the expansion of T cells after antigen challenge and by the induction of T cell apoptosis [17,19,[22][23][24]. In a number of studies, nitric oxide (NO) was identified to be an effector molecule downstream of IFN-c that was responsible for control of lymphocyte apoptosis [22,25]. Thus it has been suggested that Th1 lymphocytes can limit their own effector response via the production of IFN-c [17].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps M-1-or M-2-dominant responses evolve into dendritic cell responses that stimulate Th1 or Th2 responses, respectively. At the same time, because M-1 equates with the production of destructive molecules such as NO, overexpression of this pathway could inhibit lymphocyte responses through a suppressor macrophage effect (30,(61)(62)(63), as suggested in Fig. 6.…”
Section: M-1 or M-2 Macrophages Differentially Influence Lymphocyte Rmentioning
confidence: 99%